The Influence of Advertising Personalization and Trust on Retail Purchase Decisions Through Gen Z Consumer Engagement in Palopo City - Fitrah Rianti Fitrah; Suhardi M. Anwar; Muhammad Aqsa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of personalization and trust on retail product purchasing decisions, with Gen Z consumer engagement in Palopo City as a mediator variable. The research approach used was quantitative, with data analysis using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. Data were collected through questionnaires distributed to Generation Z respondents in Palopo City. The results showed that personalization and trust do not directly influence purchasing decisions. However, both have a positive and significant influence when mediated by consumer engagement. This finding confirms that the higher the level of consumer engagement in the interaction process with a product or service, the stronger the influence of personalization and trust in driving purchasing decisions. Thus, consumer engagement plays a key role in linking personalization and trust strategies to purchasing decisions for retail products in Palopo City. Therefore, it can be concluded that neither personalization nor trust has a direct influence on purchasing decisions, but has an indirect influence through consumer engagement with retail products in Palopo City.